2017
DOI: 10.1016/j.jgr.2016.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of Korean Red Ginseng against FK506-induced damage in LLC-PK1 cells

Abstract: BackgroundCompound FK506 is an immunosuppressant agent that is frequently used to prevent rejection of solid organs upon transplant. However, nephrotoxicity due to apoptosis and inflammatory response mediated by FK506 limit its usefulness. In this study, the protective effect of Korean Red Ginseng (KRG) against FK506-induced damage in LLC-PK1 pig kidney epithelial cells was investigated.MethodsLLC-PK1 cells were exposed to FK506 with KRG and cell viability was measured. Western blotting and RT-PCR analyses eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 26 publications
1
10
0
Order By: Relevance
“…In the case of the KRG studies, hormetic dose responses were reported using five biology models (i.e., Dermal papilla cells, Park et al [95]; A549 cell-human pulmonary epithelium cells, Song et al [16,134]; HUVEC [15]; Murine osteoblastic MC3T3 cells [129,131]; LLC-PKI cells [133]) with a focus on possible clinical translation for preventing kidney toxicity during organ transplant procedures [133] and preventing osteoporosis as a result of long-term glucocorticoid treatment [131]. In the case of kidney toxicity, it is well known that the drug FK506 plays a critical role in assuring that a patient will not reject a transplanted organ.…”
Section: Kidney Toxicitymentioning
confidence: 99%
See 2 more Smart Citations
“…In the case of the KRG studies, hormetic dose responses were reported using five biology models (i.e., Dermal papilla cells, Park et al [95]; A549 cell-human pulmonary epithelium cells, Song et al [16,134]; HUVEC [15]; Murine osteoblastic MC3T3 cells [129,131]; LLC-PKI cells [133]) with a focus on possible clinical translation for preventing kidney toxicity during organ transplant procedures [133] and preventing osteoporosis as a result of long-term glucocorticoid treatment [131]. In the case of kidney toxicity, it is well known that the drug FK506 plays a critical role in assuring that a patient will not reject a transplanted organ.…”
Section: Kidney Toxicitymentioning
confidence: 99%
“…These developments led to research showing that KRG could also be effective in preventing nephrotoxicity induced by gentamicin in rat renal tubular cells [141,142] and by chronic exposure to cyclosporine [143]. These findings led Lee et al [133] to assess whether KRG would prevent the toxicity of FK506 when both were administered at the same time. Using the LLC-PKI-pig kidney epithelial cells as their model, a toxic dose of FK506 was selected to challenge cell survival, reducing it to 60%.…”
Section: Kidney Toxicitymentioning
confidence: 99%
See 1 more Smart Citation
“…Absorbance values at 450 nm were obtained using an E-Max microplate reader (Molecular Devices, Sunnyvale, CA, USA). The viability of cells was represented by comparing the percentage of viability of the control group [30].…”
Section: Measurement Of Cell Viabilitymentioning
confidence: 99%
“…As part of a continuing search for bioactive constituents from Korean medicinal plant sources [ 12 , 13 , 14 ], the methanol (MeOH) extract of the aerial portion of L. cuneata was found to exhibit cytotoxic effects on human ovarian carcinoma cells [ 15 ]. In our recent study, bioassay-guided fractionation and repeated chromatography of the MeOH extract of L. cuneata resulted in isolation of (−)-9′- O -(α- l -rhamnopyranosyl)lyoniresinol, which suppresses the proliferation of A2780 human ovarian carcinoma cells through induction of apoptosis [ 15 ].…”
Section: Introductionmentioning
confidence: 99%